POLITIK HUKUM PEMERINTAH KOLONIAL TERHADAP PERADILAN AGAMA - Santoso, Dri (JURNAL NIZHAM, 2014)
Holand kingdom government delegation is Vereenigde oost  indische compagnie (VOC) has been  sent to Nusantara Islands at  XVI century, has goal: The first as trade mission and get result of plantation, the comodity with hight price in europe at the time. The other goal of their mission are to  colonialize new territory as market  of result industry and as resource to develope holand kingdom, beside it there is  hidden mission to spread kristen relegion.To realize of their goal have been arrangged strategy , strategy is used to break people againt. Like stratgy with aply syariah (Islamic Law) in all aspec of  life,  this policy has based on receptio in complexu  theory . this strategy has suxesful l  and has been acept by ellite local Muslim. and than becouse of anxious at Pan Islamisme Movement in Turky will Influence Nusantara Muslim. Holand Kigdom Government change their political law with limitation in many aspec. For example limitation Absholue competension in Relegious court. The policy is based receptie theory of Snauckh Hugronje. So is clear that all of political law of holand colonial or Hindia Belanda at Relegious court  to colling down muslim againts with soft politik or other way. Keywords : Law, Government, Religious courts